INCIDENCE OF OBSTETRIC AND EXTRAGENITAL PATHOLOGY IN VARIOUS-LEVEL OBSTETRIC INSTITUTIONS IN AZERBAIJAN - Mammadova, S.N. (World of Medicine and Biology, 2020)
The purpose of the work was to study the incidence of obstetric and extragenital pathology in various maternity institutions of the Republic of Azerbaijan for the period 2012-2014: in perinatal centers and district maternity hospitals. The study obstetric and extragenital pathology in obstetric institutions of various levels of the Azerbaijan Republic for the period 2012-2014 showed that oedema and proteinuria without hypertension were found to 1.2 times more often in women admitted to obstetric regional institutions of the 2nd level, premature rupture of membranes – 4 times more often, urinary tract infection and 4.7 times more often than hospitalized in institutions of the 3rd level. At the same time, in pregnant women hospitalized in level 3 institutions in 2012-2014, clinical manifestations of FNP were 1.1 times more common, and pelvic organ pathologies were 5.6 times more common than in district maternity hospitals (level 2).
Keywords: prenatal period; risk group; obstetric pathology; extragenital pathology; hospitalization; perinatal centers